Theoretical and Empirical Analysis of the Influence of Technology Gap on Carbon Emission: The Case of China - Qin Ye (MDPI AG, 2021)
Numerous studies have examined the relationship between technological development and pollution. From a global economic perspective, the narrowing of one country’s technological gap relative to the world technology frontier (due to the technological progress) may affect its environmental pollution. However, few studies have focused on this issue. This study examined the relationship between technology gap and air pollution both theoretically and empirically. The theoretical model shows that narrowing the technology gap may help reduce pollution. Using patent data from USPTO, as well as industrial level pollution and socio-economic data in China, this paper found that the narrowing of technology gap plays a role in reducing air pollution emissions in China, which confirms the theoretical model. This study provides a new perspective on the relationship between technology progress and pollution.